Analysis of Knowledge Sharing Practice Capability At Pt Pusri Palembang Factory (International Journal of Scientific Research and Management (IJSRM), 2022)
This study aims to analyze the readiness and capability of knowledge sharing practices at the PT Pusri Palembang factory related to the development of a knowledge sharing model at the largest fertilizer factory in Indonesia, namely PT Pusri Palembang. This research is quantitative descriptive. Data was collected through participant observation, document study, recording, and distributing questionnaires. This study focuses on analyzing the readiness and ability of workers in factories to share knowledge where the component analyzed is the informal learning component, the process of sharing knowledge between employees where knowledge stored in individual employees is shared and accumulated to all employees in various work units to improve company memory and corporate intelligence. This research produces a score of readiness and capability of the work unit and the data is obtained through a survey questionnaire which is distributed directly to factory employees who have carried out knowledge sharing, whose questions contain a kind of assessment from employees who share knowledge. Prior to data collection, the researcher selected and sorted out the components in the 70:20:10 learning and development model and shared knowledge only for those components of informal learning that intersect or intersect between. In this study, an analytical model of practice measurement and knowledge sharing skills was produced as a research innovations.